2021
DOI: 10.1590/1982-0224-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology aspects of Alopias pelagicus and A. superciliosus (Lamniformes: Alopiidae) in the Ecuadorian Pacific

Abstract: The reproductive biology of thresher shark species of the Ecuadorian Pacific was analysed based on 1236 specimens of Alopias pelagicus (711 females and 525 males) and 354 of A. superciliosus (164 females and 190 males) landed in “Playita Mía”, from January to December of 2019. The length of A. pelagicus females ranged between 67.2 and 184 cm PCL (precaudal length) and the males between 69.0 and 178.4 cm PCL, A. superciliosus registered a minimum and maximum size of 76.0 and 202.2 cm PCL for females and 94.0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In addition, the high flow of genes into the population per generation also affects the genetic closeness of the two populations. Bigeye thresher shark (A. superciliosus) can migrate a great distance of more than 1500 miles (Briones-Mendoza et al 2021) and is a good swimmer (Frumkin and Shimada 2020). Thus, seasonal changes in abundance and distribution are thought to reflect seasonal migrations in latitude associated with changes in water temperature (Morales et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the high flow of genes into the population per generation also affects the genetic closeness of the two populations. Bigeye thresher shark (A. superciliosus) can migrate a great distance of more than 1500 miles (Briones-Mendoza et al 2021) and is a good swimmer (Frumkin and Shimada 2020). Thus, seasonal changes in abundance and distribution are thought to reflect seasonal migrations in latitude associated with changes in water temperature (Morales et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the total length and length of the clasper of A. pelagicus is sigmoid, meaning that as the total length of the body increases, the length of the clasper also increases until it reaches its maximum length [13]. The results of the analysis from the study of Briones-Mendoza et al [19], showed a decrease in the average size of male A. pelagicus worldwide. This decline can be • The length of female A. pelagicus varies from 67.2 to 184 cm PCL, while males range from 69.0 to 178.4 cm PCL.…”
Section: Reproduction Of a Pelagicusmentioning
confidence: 99%
“…The biological aspects of Alopias pelagicus and Alopias superciliosus were previously published by Briones-Mendoza et al (see [36]).…”
Section: Family Alopiidaementioning
confidence: 99%